Measurement of Projections Between Dentate Nucleus and Contralateral Frontal Cortex in Human Brain Via Diffusion Tensor Tractography - Ji, Qing; Edwards, Angela; Glass, John O.; Brinkman, Tara M.; Patay, Zoltan; Reddick, Wilburn E. (Cerebellum (London, England), 2019)
We propose a probabilistic fiber-tracking scheme to reconstruct the fiber tracts between the dentate nucleus (DN) in the cerebellum and the entire contralateral cerebral frontal cortex in the human brain. We assessed diffusion tensor imaging (DTI) data from 39 healthy controls. The connection fibers between the DN and contralateral frontal cortex of all subjects were successfully reconstructed and studied. We demonstrated that multi-fiber probabilistic models must be used to resolve the challenge of crossing fibers. We also demonstrated that the entire pathway can be reconstructed without using any synaptic regions of interest along the path and that the reconstructed tracts connected the ipsilateral superior cerebellar peduncle, contralateral red nucleus, and ventral lateral and ventral anterior nuclei of thalamus in the path traveling to the contralateral frontal cortex. The fibers in the pathway projected into all areas of the contralateral frontal cortex but were predominantly located in the primary motor and premotor areas. A large portion of fibers terminated in the prefrontal cortex, which included dorsolateral prefrontal areas, anterior prefrontal areas, and the Broca language area. Our findings provide robust, reproducible, and direct DTI-based evidence that the DN through the efferent cerebellar pathway has considerable contribution to high-level executive functions of the human brain.